SUSTAINABLE USE OF LIME SLUDGE AND METAKAOLIN IN THE CONSTRUCTION INDUSTRY TO STRENGTHEN SUSTAINABLE DEVELOPMENT GOALS (SDGS): A REVIEW - Chouksey , Arti; Dev, Nirendra (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Construction is one of the most resource-intensive industries, requiring massive amounts of raw materials and causing greenhouse gas emissions, waste, and environmental destruction. With growing global pressure to adopt sustainable practices, reusing industrial byproducts like lime sludge and adding supplementary cementitious materials like metakaolin can reduce environmental footprints and improve construction material performance. Lime sludge, a high-calcium industrial waste from pulp and paper, chemical, and water treatment sectors, is volumetric and chemically reactive, making disposal difficult. In contrast, metakaolin, a highly reactive pozzolanic material made from thermally treated kaolinite clay, is suited for cement replacement due to its high surface area, amorphous silica concentration, and calcium hydroxide reactivity. This review study synthesises literature on lime sludge and metakaolin's chemical composition, mechanical behaviour, pozzolanic activity, and environmental effect to examine their synergistic potential in building. The review emphasises their function in compressive strength, permeability reduction, durability, and circular economy. The paper also links these materials to Sustainable Development Goals (SDGs) 9 (Industry, Innovation, and Infrastructure), 11 (Sustainable Cities and Communities), and 12 (Responsible Consumption and Production) to promote eco-efficiency, responsible waste management, and sustainable infrastructure. Discussing economic feasibility, environmental performance, and technical flexibility highlights their practical consequences for large-scale adoption. The review concludes by identifying challenges like material quality variability, lack of standardised guidelines, and awareness barriers and suggesting future research and policy development to mainstream these materials into sustainable construction practises.